Constructing N, P-dually doped biochar materials from biomass wastes for high-performance bifunctional oxygen electrocatalysts. (September 2021) - Ma, Lin-Lin; Hu, Xiao; Liu, Wu-Jun; Li, Hong-Chao; Lam, Paul K.S.; Zeng, Raymond Jianxiong; Yu, Han-Qing
Abstract: The large scale lignocellulosic biomass wastes could also be regarded as abundantly-available renewable resources, and how to convert them into value-added products via sustainable approaches is still a big challenge. In this work, we demonstrated a facile pyrolysis method to construct N, P-dually doped biochar materials from the lignocellulosic biomass wastes. The as-synthesized N, P-dually doped biochar samples could act as electrocatalysts for oxygen reduction and evolution reactions (ORR/OER), showing excellent catalytic performance and long-term durability, as well as robust tolerance to CO and methanol. The unique hierarchical porous structure, favorable electronic structure modified by the N and P doping, as well as a variety of defect sites induced by the N and P doping into the carbon framework were identified as the main contributions to the prominent catalytic activity of the as-synthesized N, P-dually doped biochar materials. We expect this work would spur more efforts into developing advanced materials from the large scale lignocellulosic biomass wastes. Graphical abstract: Image 1 Highlights: N, P doped biochar was synthesized via a facile thermochemical method from biomass wastes. The N, P doped biochar exhibited robust bifunctional electrocatalytic activity. The unique porous structure and electronic structure were attributed to its excellent activity.